1997
DOI: 10.2337/diab.46.12.1950
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Captopril, Losartan, and Bradykinin on Early Steps of Insulin Action

Abstract: Insulin initiates its metabolic and growth-promoting effects by binding to the alpha subunit of its receptor, thereby activating the kinase in the beta subunit. This event leads to tyrosyl phosphorylation of its cytosolic substrate, insulin receptor substrate 1 (IRS-1), which in turn associates with and activates phosphatidylinositol (PI) 3-kinase. The clinical use of ACE inhibitors has been associated with increased insulin sensitivity. However, the exact molecular mechanism is unknown. In the present study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(53 citation statements)
references
References 43 publications
1
52
0
Order By: Relevance
“…The proteins were treated with Laemmli sample buVer containing dithiothreitol and boiled for 5 min before loading onto 8% SDS-PAGE in a Bio-Rad miniature slab gel apparatus. Similar sized aliquots (90 g) were subjected to SDS-PAGE as described elsewhere (Carvalho et al 1997). Electrotransfer of proteins from the gel to nitrocellulose was performed for 1 h at 120 V (constant) in a Bio-Rad miniature transfer apparatus.…”
Section: Protein Analysis By Immunoblottingmentioning
confidence: 99%
“…The proteins were treated with Laemmli sample buVer containing dithiothreitol and boiled for 5 min before loading onto 8% SDS-PAGE in a Bio-Rad miniature slab gel apparatus. Similar sized aliquots (90 g) were subjected to SDS-PAGE as described elsewhere (Carvalho et al 1997). Electrotransfer of proteins from the gel to nitrocellulose was performed for 1 h at 120 V (constant) in a Bio-Rad miniature transfer apparatus.…”
Section: Protein Analysis By Immunoblottingmentioning
confidence: 99%
“…The supernatant was either used for immunoprecipitation with anti-IR, anti-IRS-1, anti-IRS-2 and protein A-Sepharose 6MB or treated as whole extract tissues with Laemmli sample buffer treatment and electrophoresis in SDS-PAGE as described elsewhere (Carvalho et al, 1996(Carvalho et al, , 1997. For whole tissue extracts, similar sized aliquots (200 Ag protein) were subjected to SDS-PAGE and immunoblotted with anti-phospho-AKT or anti-phospho-PKC antibodies.…”
Section: Protein Analysis By Immunoblottingmentioning
confidence: 99%
“…In fact, evidences that bradykinin stimulates the insulin signaling pathway were already reported (Isami et al, 1996) and its potential effect to enhance early steps of insulin signal in liver, after ACE inhibition, was also proposed (Carvalho et al, 1997). Furthermore, it was shown that the ethanol metabolite, acetaldehyde, inhibits ACE activity and might mediate systemic increase in bradykinin (Thevananther and Brecher, 1993).…”
Section: Discussionmentioning
confidence: 94%
“…A potential mechanism involves the renin-angiotensin-system (RAS) and bradykinin. It is known that angiotensin-converting enzyme (ACE) inhibition improves the in vivo insulin sensitivity (Carvalho et al, 1997;Prada et al, 2000) and it has been claimed that initial steps of insulin signaling are enhanced in rats treated with ACE inhibitor (Carvalho et al, 1997;Nawano et al, 1999). However, the block of the angiotensin receptor 1 with losartan had no similar effect, suggesting that the ACE inhibition effect does not involve the .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation